2010
DOI: 10.1111/j.1540-8167.2010.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Mechanical Consequences of Permanent Right Ventricular Pacing: Effect of Pacing Site

Abstract: Long-term RVOT-pacing was associated with superior indices of LV structure and function compared with RVA-pacing, and was associated with less adverse LA remodeling. If pacing cannot be avoided, the RVOT septum may be the preferred site for right ventricular pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 23 publications
(36 reference statements)
1
72
0
2
Order By: Relevance
“…In the remaining patients, there was no difference in QRS duration. Many recent studies have compared the mechanic synchrony between septal pacing and RVA pacing (Schwaab et al, 1999;Yu et al, 2007;Flevari et al, 2009;Ng et al, 2009;Takemoto et al, 2009;Leong et al, 2010;Cano et al, 2010;Yoshikawa et al, 2010) and have showed a more inter and intraventricular synchrony with septal pacing than apical pacing immediately after implantation and at midterm (after 6 to 12 months of follow-up), excepted for the study of Ng et al (Ng et al, 2009). Moreover, patients in the RVAP group had significantly more inter and intraventricular dyssynchrony than did the controls, and patients in the RVSP group had comparable values to those obtained from the control group (Flevari et al, 2009;Verma et al, 2010;Cano et al, 2010).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 99%
See 4 more Smart Citations
“…In the remaining patients, there was no difference in QRS duration. Many recent studies have compared the mechanic synchrony between septal pacing and RVA pacing (Schwaab et al, 1999;Yu et al, 2007;Flevari et al, 2009;Ng et al, 2009;Takemoto et al, 2009;Leong et al, 2010;Cano et al, 2010;Yoshikawa et al, 2010) and have showed a more inter and intraventricular synchrony with septal pacing than apical pacing immediately after implantation and at midterm (after 6 to 12 months of follow-up), excepted for the study of Ng et al (Ng et al, 2009). Moreover, patients in the RVAP group had significantly more inter and intraventricular dyssynchrony than did the controls, and patients in the RVSP group had comparable values to those obtained from the control group (Flevari et al, 2009;Verma et al, 2010;Cano et al, 2010).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 99%
“…Previous investigations of alternative pacing sites have yielded inconsistent results (Mera et al, 1999;Giudici et al, 1997;Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Tse et al Europace 2009;Victor et al, 1999) which may be attributable, in part, to the fact that the pacing site was determined on a topological rather than functional basis (Giudici & Karpawich, 1999). Many previous studies (Schwaab et al, 1999;Victor et al, 2006;Yu et al, 2007;Ng et al, 2009;Takemoto et al, 2009;Tse et al, Europace 2009, Gong et al, 2009Leong et al, 2010;Schwaab et al, 2001), have showed that septal pacing induced shorter paced QRS duration than RVA pacing did. These results indicated that RVS pacing resulted in better electric synchrony compared with RVA pacing.…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 99%
See 3 more Smart Citations